The two-layered radiative transfer model for snow reflectance and its application to remote sensing of the Antarctic snow surface from space - Kokhanovsky, Alexander; Brell, Maximilian; Segl, Karl; Efremenko, Dmitry; Petkov, Boyan; Bianchini, Giovanni; Stone, Robert; Chabrillat, Sabine (Frontiers in Environmental Science, 2024)
The two-LAyered snow Radiative Transfer (LART) model has been proposed for snow remote sensing applications. It is based on analytical approximations of the radiative transfer theory. The geometrical optics approximation has been used to derive the local snow optical parameters such as the probability of photon absorption by ice grains and the average cosine of single light scattering in a given direction in snowpack. The application of the model to the selected area in Antarctica has shown that the technique is capable to retrieve the snow grain size both in upper and lower snow layers with sizes of grains larger in the lower snow layer as one might expect due to the metamorphism processes. Such a conclusion is confirmed by ground measurements of the vertical snow grain size variability in Antarctica.